The Evolution of Clinician-Academics in Paramedicine: Completing the Picture of Professionalism. Issue 5 (5th October 2022) - Meadley, Ben N.; Andrews, Tim; Delardes, Belinda J.; Shannon, Brendan P.
Abstract: Paramedicine is an evolving and integral component of the health system, though the profession has historically relied on medicine and nursing to drive a research agenda. Now, with a well-established research presence, still lacking is the formalized role of the clinician-academic. In this opinion piece, the authors detail how paramedic clinician-academics can drive the profession forward, contribute to enhanced patient care, systems design, and staff well-being.